2017
DOI: 10.1021/acs.jpcc.7b01334
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Luminescence Intensity in Red Emitting NaYF4:Yb/Ho/Mn Upconversion Nanophosphors by Variation of Reaction Parameters

Abstract: In the field of biomedicine, upconversion nanoparticles have wide ranging applications from bioimaging to targeted cargo delivery, especially due to their excellent chemical and optical properties in comparison with conventional fluorophores. However, their use in biomedical applications is largely hindered due to strong absorption of short wavelength (<600 nm) light by biological tissues/cells and feeble luminescence. Hence, it is important to develop new strategies to increase the long wavelength (red) emiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…Here we have shown the PVP40-mediated UCNP synthesis method can be used to create UCNPs with strong red emission via Mn 2+ co-doping. Prior studies have shown that Mn 2+ co-doping can dramatically improve red emission in a variety of UCNP morphologies produced via solvothermal and hydrothermal methods [22,40,[50][51][52][53][54][55]. An important mechanism for this red emission improvement is that Mn 2+ co-doping encourages formation of pure α-phase UCNP structure, which is well suited for red emission due to larger unit cell size than the smaller unit cells of β-phase UCNPs [40,55].…”
Section: Resultsmentioning
confidence: 99%
“…Here we have shown the PVP40-mediated UCNP synthesis method can be used to create UCNPs with strong red emission via Mn 2+ co-doping. Prior studies have shown that Mn 2+ co-doping can dramatically improve red emission in a variety of UCNP morphologies produced via solvothermal and hydrothermal methods [22,40,[50][51][52][53][54][55]. An important mechanism for this red emission improvement is that Mn 2+ co-doping encourages formation of pure α-phase UCNP structure, which is well suited for red emission due to larger unit cell size than the smaller unit cells of β-phase UCNPs [40,55].…”
Section: Resultsmentioning
confidence: 99%
“…However, there are lot of conditions are involved including type of surfactant and its concentration, precursors concentration, reaction temperature, type of solvent and its composition, reaction time, etc., hence, it is difficult to determine most optimized experimental conditions for one specific reaction and nanocrystals growth process also cannot be observed in this approach. Lately our group has reported an effective approach for the improvement of red luminescence of UCNP by altering the various reaction parameters through hydrothermal synthesis ( Figure ) . In this work, the effect of various synthesis parameters, such as reaction temperature, time and solvent ratio on morphology, crystal phase and the luminescence UCNP has been investigated in detail and optimized.…”
Section: Synthesis Strategiesmentioning
confidence: 99%
“…Schematic representation of hydrothermal synthesis of NaYF 4 :Yb/Ho/Mn in various reaction parameters. Reproduced with permission . Copyright 2017, ACS Publishers.…”
Section: Synthesis Strategiesmentioning
confidence: 99%
“…Lanthanide-doped materials possess the features such as narrow emission bands, long luminescence lifetime, excellent photostability, and low cytotoxicity, , which make them appropriate for many luminescence applications. They can be excited in the NIR region of the spectrum and act as a medium to transduce NIR to well-defined emission peaks extending from NIR to the UV region via a multiphoton upconversion process. Among them, Yb 3+ /Tm 3+ -codoped fluorides with NIR-to-UV upconversion luminescence (UCL) have drawn great attention due to the significance of UV emission in materials science and biological studies. The low upconversion quantum yield in lanthanide-doped nanocrystals, nonetheless, is a serious restriction for their widespread applications.…”
Section: Introductionmentioning
confidence: 99%